(3efJNHGJ ef cJGH (B"(3dH GdCdHGH(B"s - (3CMeO GdCTYQis
(3BNQgG (B:s
(3BNQ eG ajg McGjI SdjeGf Hf YHOGdedc eY MGRe GdCYQL s
(3HOhf JGQjNs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 s
Keywords: (3GdCOHs